2017
DOI: 10.1371/journal.pone.0170460
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Speciation and Gene Flow between Taxonomically Challenging Trochulus Species Complex (Gastropoda: Hygromiidae)

Abstract: Geographical isolation, selection and genetic drift can cause the geographical diversification of populations and lead to speciation. Land snail species in the genus Trochulus show overlaps in geographical ranges as well as in morphology, but genetic data do not always support the species-level taxonomy based on morphological characters. Such a group offers an excellent opportunity to explore the processes involved. We have addressed the problem by determining the status of the restricted endemic T. graminicol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 65 publications
(99 reference statements)
1
13
0
Order By: Relevance
“…Our integrative study allowed to recognise it as a separate taxon. Previous phylogenetic analyses based on the COI gene showed that T. coelomphala is most closely related to T. graminicola (Falkner, 1973), an endemic species known only from its type locality in south-western Germany, about 200 km away from the T. coelomphala location (Proćków et al, 2017c). However, using four molecular markers, we found that T. coelomphala sequences are grouped within T. hispidus and are closely related with its samples found in the Bavarian Alps in phylogenetic trees (Figure 8, Figures S3 and S4).…”
Section: Validity Of Trochulus Coelomphala As Taxon and Its Originmentioning
confidence: 99%
See 4 more Smart Citations
“…Our integrative study allowed to recognise it as a separate taxon. Previous phylogenetic analyses based on the COI gene showed that T. coelomphala is most closely related to T. graminicola (Falkner, 1973), an endemic species known only from its type locality in south-western Germany, about 200 km away from the T. coelomphala location (Proćków et al, 2017c). However, using four molecular markers, we found that T. coelomphala sequences are grouped within T. hispidus and are closely related with its samples found in the Bavarian Alps in phylogenetic trees (Figure 8, Figures S3 and S4).…”
Section: Validity Of Trochulus Coelomphala As Taxon and Its Originmentioning
confidence: 99%
“…In particular, the T. hispidus complex exemplifies problems in species delimitation. DNA barcoding in the absence of detailed phylogeographic relationships (Duda et al, 2014) has not been successful (Kruckenhauser et al, 2014;Pfenninger et al, 2005;Proćków et al, 2017c). Here, we included four genetic markers in an effort to obtain relationships within and among species of Trochulus with a greater resolution.…”
Section: Geographic Pattern and Evolutionary Relationships Among CLmentioning
confidence: 99%
See 3 more Smart Citations